2013
DOI: 10.1128/jvi.01927-13
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination in E3 Genes of Human Adenovirus Species D

Abstract: e Genes within the E3 transcription unit of human adenoviruses modulate host immune responses to infection. A comprehensive genomics and bioinformatics analysis of the E3 transcription unit for 38 viruses within human adenovirus species D (HAdV-D) revealed distinct and surprising patterns of homologous recombination. Homologous recombination was identified in open reading frames for E3 CR1␣, CR1␤, and CR1␥, similar to that previously observed with genes encoding the three major structural capsid proteins, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 84 publications
6
57
0
1
Order By: Relevance
“…Both recombination between species D types and selection of novel neutralization epitopes ('immune escape') contribute to this diversity (Robinson et al, 2011aSingh et al, 2013). Except for a few types that cause epidemic keratoconjunctivitis (a severe eye infection), most of the types of HAdV-D are not associated with severe diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Both recombination between species D types and selection of novel neutralization epitopes ('immune escape') contribute to this diversity (Robinson et al, 2011aSingh et al, 2013). Except for a few types that cause epidemic keratoconjunctivitis (a severe eye infection), most of the types of HAdV-D are not associated with severe diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, these genome regions originate from a common ancestor, and several recombination events placed them in the four distinct HAdV types. Singh et al (2013) identified the E3 region of the genome as a hot-spot for recombination events, and grouped the HAdV-27/28 CR1-beta proteins into one proteotype. The corresponding proteins of HAdV-70 and -84 can also be classified into the same proteotype 9 cluster.…”
mentioning
confidence: 99%
“…It also indicates the significance of classifying worldwide HAdV isolates, including the identification of new proteotyping combinations, in these regions. Meanwhile, a recent report concluded that the CR1 genes in the early transcription unit 3 (E3) region are a hot spot for recombination among HAdV-D types (35). The proteins encoded within the E3 region are crucial for modulating the host immune response during virus infection, although it has not been reported that host neutralizing antibodies affect these proteins (36,37).…”
Section: Discussionmentioning
confidence: 99%